2022
DOI: 10.3389/fonc.2022.899925
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Immune-Related Long Non-Coding RNA Signature for Predicting Immunotherapeutic Response and Prognosis in NSCLC Patients Treated With Immunotherapy

Abstract: BackgroundNumerous studies have reported that long non-coding RNAs (lncRNAs) play important roles in immune-related pathways in cancer. However, immune-related lncRNAs and their roles in predicting immunotherapeutic response and prognosis of non-small cell lung cancer (NSCLC) patients treated with immunotherapy remain largely unexplored.MethodsTranscriptomic data from NSCLC patients were used to identify novel lncRNAs by a custom pipeline. ImmuCellAI was utilized to calculate the infiltration score of immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…In the phase I KEYNOTE-001 study, the subgroup of individuals with metastatic melanoma was analyzed; the highest rate of CR (42.3%) was in lung lesions, followed by peritoneal (37.3%) and liver (24.4%) ( 23 ). The findings of this research are in line with the recently published NSCLC cohort by researchers demonstrating higher OSRR and OSDCR in patients with lymph node metastases, also supporting the concept of better response in organs with postulated high pre-treatment immune cell infiltration ( 24 ). In addition, the discoveries in this study substantiate previously published studies reporting poorer activities in liver metastases ( 25 ), where the liver exhibits suppressive immune modulation attributes ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…In the phase I KEYNOTE-001 study, the subgroup of individuals with metastatic melanoma was analyzed; the highest rate of CR (42.3%) was in lung lesions, followed by peritoneal (37.3%) and liver (24.4%) ( 23 ). The findings of this research are in line with the recently published NSCLC cohort by researchers demonstrating higher OSRR and OSDCR in patients with lymph node metastases, also supporting the concept of better response in organs with postulated high pre-treatment immune cell infiltration ( 24 ). In addition, the discoveries in this study substantiate previously published studies reporting poorer activities in liver metastases ( 25 ), where the liver exhibits suppressive immune modulation attributes ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, we extra used the transcriptional sequencing data of GIAC patients and immunotherapy response status of melanoma and urothelial carcinoma patients to assess the value of TMEscore. Though this method often used in previous studies [59][60][61][62][63][64] can be serve as a tentative and preliminary expansion application, it is indeed biased and not rigorous. When relevant data is publicly available in the future, we can precisely assess the predicted value of TMEscore in matched datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that lncRNAs LCETRL3 and LCETRL4 on chromosome 4q12 reduce the therapeutic sensitivity of EGFR-TKI in NSCLC by stabilizing TDP43 and EIF2S1 [11]. Ma et al have constructed an immunotherapeutic response and immune-related (ITIR)-lncRNA signature, which can be used to predict the immunotherapy response and prognosis of NSCLC patients receiving immunotherapy [12]. Ling et al demonstrated that the level of exosomal lncRNA RP5-977B1 has high diagnostic ability and prognostic value in NSCLC because it is higher than that in the healthy control group [13].…”
Section: Introductionmentioning
confidence: 99%